Langerhans Cell Histiocytosis Associated With Renal Cell Carcinoma Is a Neoplastic Process: Clinicopathologic and Molecular Study of 7 Cases. (December 2020) - Agaimy, Abbas; Bonert, Michael; Naqvi, Asghar; Wang, Chunjie; Trpkov, Kiril; Dettmar, Peer; Wintzer, Hanns-Olof; Stoehr, Robert; Hes, Ondřej; Williamson, Sean R.; Gibson, Ian W.; Hartmann, Arndt
Abstract : Langerhans cell histiocytosis (LCH) is a rare histiocytic disorder composed of Langerhans cells admixed with reactive mononuclear and granulocytic cells, associated with prominent eosinophils. LCH is considered a neoplasm, driven in most cases by oncogenic RAS/RAF/MEK/ERK pathway mutations. The disease predominantly affects children. Urinary system involvement has rarely been reported in a multisystem disease setting. We describe 7 patients who presented with LCH occurring within (6 cases) or after (1 case) a resected clear cell (n=6) or clear cell papillary (n=1) renal cell carcinoma (RCC), identified prospectively in our routine and consultation files (2012 to 2019). The patients included 5 women and 2 men, with a median age of 54 years (range, 39 to 73 y), none with a history of LCH or LCH manifestations before the time of RCC diagnosis. The median size of the RCC was 3.5 cm (range, 1.8 to 8.3 cm). Treatment included partial (5 cases), or radical (2 cases) nephrectomy. All RCCs on gross examination showed at least focal cystic changes and were low grade (World Health Organization [WHO]/International Society of Urologic Pathologists [ISUP] grade 1 to 2). The LCH foci were detected as incidental histological finding within the resected RCC in all six cases and they were limited to few high-power fields (<2 mm 2 ) in 5 of 6 cases, but in the sixth case, they occupied almost the entire clear cell papillary RCC (2 cm nodule). No LCH manifestations were detected in the normal kidney or in perinephric fat. The seventh patient developed LCH within inguinal deep soft tissue followed by systemic manifestations 6 years after clear cell RCC. Langerhans cell immunophenotype was supported by the reactivity for S-100, CD1a, and langerin and by the negative pankeratin. Successful pyrosequencing of microdissected LCH DNA revealed the V600E BRAF mutation in all 6 cases of LCH within RCC. To our knowledge, only 3 similar cases were published since 1980; the only case tested for BRAF mutation showed wild-type BRAF . This is the first study analyzing the morphologic and genetic features of a cohort of LCH associated with RCC. In our experience, these cases may be underrecognized in practice, or may erroneously be diagnosed as RCC dedifferentiation or high-grade sarcomatoid transformation. Finally, the detection of BRAF mutation further confirms that LCH in this setting is indeed a neoplasm, rather than a reactive lesion.